The inflammatory reaction Of Hepatitis B Virus Patients - AnokNjum, Ali; Abdul-Hassan, Layla Saleh; Hashem , Ihasan A (International Journal of Psychosocial Rehabilitation, 2019)
study aim to estimate immune molecules CD54 & CD74 and TNF-B and IL-8 in patients infected with HBV , A total of (80) seropositive patients for HBV were screened for this study to know level of TNF-B & IL-8 in serum of patient and show expression of CD54 and CD74. Results showed that serum samples were analyzed for IL-8 & TNF-B by ELISA , showed highly significant increases (p